Depth‐Resolved Groundwater Chemistry by Longitudinal Sampling of Ambient and Pumped Flows Within Long‐Screened and Open Borehole Wells. Issue 11 (19th November 2019) - Poulsen, David L.; Cook, Peter G.; Simmons, Craig T.; Solomon, D. Kip; Dogramaci, Shawan
Abstract: Depth‐resolved chemistry samples are critical to a wide range of groundwater investigations. If a well intersects zones of variable concentrations, a pumped sample is a composite of the inflows, which mix in the well. Where discrete concentrations are required, excessive mixing makes samples less useful and potentially misleading. However, installations for depth‐discrete sampling are expensive, particularly for regional studies, so sometimes there is incentive to use existing infrastructure designed for other purposes (e.g., supply wells). This paper shows how the resolution of groundwater chemistry derived from long‐screened and open borehole wells can be improved by measuring and sampling the in‐well vertical flow regimes in ambient (unpumped) and/or pumped conditions. The ambient flow regime, driven by a natural vertical head gradient, is shown to be particularly useful to sample groundwater native to defined inflow zones (head in the zone > head in the well) and avoid zones impacted by the invasion of intraborehole flow (head in the zone < head in the well). Depth‐specific samples are interpreted either as native groundwater from a discrete source, subject only to analytical error, or a mixture from multiple sources that can be deconvolved, incorporating error in both flow and concentration measurements. Depth‐resolved age tracers (chlorofluorocarbons, 14 C, and He) in groundwater from three supply wells are verified with samples from a multidepth nest of piezometers. Results show old groundwater at all depths and the simultaneous occurrence of young water at shallower depths in undisturbed dual‐porosity fractured aquifers in the Pilbara region of Western Australia. Key Points: Sampling ambient vertical flows can provide more insightful data than sampling pumped flows Ambient flows can be sampled without purging or pumping the well In‐well samples are either from a discrete source or the mixture that can be deconvolved